(untitled) (Agroindustria, Sociedad y Ambiente, 2020)
Solanum nigrum is a solanaceous plant widely distributed in tropical regions, traditionally used for the treatment of various pathologies. The objective of this research was to carry out a search in bibliographical bases of scientific information, to establish the relation of the pharmacological properties attributed to the plant with the presence of secondary metabolites. The results reveal that S. nigrum is of massive use with pharmacological purposes, being the extracts prepared with the leaves and fruits of the plant the most used for antipyretic and dermatological analgesic purposes. The systematic review of literature in the database attributes the pharmacological potential of the plant to the concentration of secondary metabolites in the reproductive and vegetative organs of the plant